The IMPACT OF CRYPTOCURRENCY ON THE TRADITIONAL BANKING SYSTEM IN INDONESIA: A THREAT OR COMPLEMENT - Benediktus Rolando (Jurnal Akuntansi dan Bisnis, 2025)
This study explores the relationship between cryptocurrency and the traditional banking system in Indonesia, aiming to determine whether cryptocurrency acts as a threat or a complement to conventional banking practices. The research employs a systematic literature review methodology, conducting extensive searches through the Scopus and Google Scholar databases to gather relevant data and insights. The rapid growth and adoption of cryptocurrencies, particularly Bitcoin, have revolutionized financial interactions by providing decentralized alternatives that enhance transaction efficiency and reduce costs, thereby challenging the established norms of the traditional banking system. The study reveals the dual nature of cryptocurrencies, highlighting their potential to compete with traditional banks while also presenting opportunities for innovation through the integration of blockchain technology, which can improve transparency and security in financial transactions. The regulatory environment in Indonesia plays a crucial role in shaping the dynamics between cryptocurrency and the banking sector. Currently, cryptocurrencies are classified as commodities, but the legal framework remains ambiguous, potentially exposing banks to risks such as money laundering and fraud. The findings emphasize the importance of establishing a balanced regulatory approach that can effectively harness the benefits of cryptocurrency while mitigating its associated risks. By doing so, Indonesia can foster an environment where both traditional banks and digital currencies can coexist and thrive, contributing to the development of a more robust and inclusive financial ecosystem.